THE VALUE RELEVANCE OF FINANCIAL INFORMATION AND NON FINANCIAL INFORMATION: SUSTAINABILITY REPORTING AND GREEN ACCOUNTING IN INDONESIA - Puspa, Dwi Fitri; Novianti, Neva; Nazaruddin, Ietje (Media Riset Akuntansi, Auditing & Informasi, 2025)
This study examines the value relevance of financial and non-financial information in the Indonesian capital market. Specifically, it aims to: (i) assess the value relevance of financial information represented by earnings and book value; (ii) evaluate whether non-financial information, proxied by sustainability reporting and green accounting practices, is value-relevant; and (iii) investigate the effect of green accounting on earnings sustainability. The sample comprises 69 consumer non-cyclical companies listed on the Indonesia Stock Exchange, covering the Food & Staples Retailing, Beverages, Processed Foods, Agricultural Products, Tobacco, Household Products, and Personal Care Products sectors during the 2018–2022 period. Using a regression-based framework grounded in the Ohlson (1995) valuation model and an earnings persistence approach, this study analyzes the association between accounting information, firm value, and earnings sustainability. The findings indicate that financial information, namely earnings and book value, is value-relevant and significantly explains variations in market value. In contrast, non-financial information in the form of sustainability reporting and green accounting does not exhibit value relevance. However, green accounting is found to have a positive effect on earnings sustainability, suggesting an improvement in earnings quality. These results provide important implications for investors and regulators regarding how the Indonesian capital market evaluates sustainability-related disclosures and green accounting practices, particularly from the perspectives of value relevance and earnings persistence.